Research on integrated injection-production optimization technology of electric submersible pump for Bohai oilfield heavy oil thermal recovery - Li Menglong; Yu Jifei; Hao Tongchun; Cao Yanfeng; Yang Yang; Yan Xinjiang; Liu Zhilong; Liu Fengxun; Li Lingxi; Dong Shichao (Journal of Petroleum Exploration and Production Technology)
Abstract The geological reserves of ordinary heavy oil suitable for thermal injection development in Bohai Oilfield are about 450 million tons. The traditional thermal recovery process uses a two trip injection-production string development method, which frequently starts and stops operations, resulting in additional cold damage and high costs. The efficiency of the jet pump injection-production integrated string system is also low, and production control is difficult. Therefore, based on the results of an integrated field test of electric submersible pump injection and production, this article optimizes its key technologies, removes high-temperature downhole on-off valves, re develops high-temperature deep well exhaust valves, and optimizes the structure of the packer as the installation platform for deep well exhaust valves. Indoor and field tests were conducted, and the results showed that the improved integrated technology of electric submersible pump injection and production met the requirements of 250 ℃ - room temperature and 21 MPa dynamic sealing. It can achieve multiple rounds of non repair injection and production conversion under steam throughput development mode, while reducing platform space requirements and injection heat loss, improving system efficiency and economy. The integrated optimization technology of electric submersible pump injection and production has good stability and applicability, and can be further promoted and applied.